Structural and Functional Evidence for Testosterone Activation of GPRC6A in Peripheral Tissues - Pi, Min (Mol Endocrinol, 2015)
G protein-coupled receptor (GPCR) family C group 6 member A (GPRC6A) is a multiligand GPCR that is activated by cations, L-amino acids, and osteocalcin. GPRC6A plays an important role in the regulation of testosterone (T) production and energy metabolism in mice. T has rapid, transcription-independent (nongenomic) effects that are mediated by a putative GPCR. We previously found that T can activate GPRC6A in vitro, but the possibility that T is a ligand for GPRC6A remains controversial. Here, we demonstrate direct T binding to GPRC6A and construct computational structural models of GPRC6A that are used to identify potential binding poses of T. Mutations of the predicted binding site residues were experimentally found to block T activation of GPRC6A, in agreement with the modeling. Using Gpr6ca(−/−) mice, we confirmed that loss of GPRC6A resulted in loss of T rapid signaling responses and elucidated several biological functions regulated by GPRC6A-dependent T rapid signaling, including T stimulation of insulin secretion in pancreatic islets and enzyme expression involved in the biosynthesis of T in Leydig cells. Finally, we identified a stereo-specific effect of an R-isomer of a selective androgen receptor modulator that is predicted to bind to and shown to activate GPRC6A but not androgen receptor. Together, our data show that GPRC6A directly mediates the rapid signaling response to T and uncovers previously unrecognized endocrine networks.